CHANNEL DEPOSITS AND BEDFORMS IN THE SEPOTUBA-PARAGUAY RIVER CONFLUENCE ENVIRONMENT, UPPER PANTANAL, MATO GROSSO STATE, BRAZIL - Leandro, Gustavo Roberto dos Santos; Rocha, Paulo Cesar [UNESP]; Hurtado, Manoel Diego Santos (Univ Estado Rio Janeiro, 2023)
This study aimed to analyze the morphological evolution in the lower course of the Sepotuba River, its confluence with the Paraguay River, and the Upper Pantanal in Mato Grosso, Brazil, especially the stages of depositional processes and forms from different space-time scales. Thus, the research was conducted considering the following: a) office stages with a preliminary and continued review, systematization, statistical analysis, and data representation based on cartographic bases thematic mapping; b) field and laboratory steps for monitoring and determining the granulometric characteristics of the sediments deposited in the fluvial environments. The main results indicate that the water flow in the Sepotuba river system reoccupies and abandons floodplain stretches due to avulsions, pendulum cuts, and lateral migration. In this context, it currently has two fluvial channels-main and secondary-that connect to the Paraguay River. Considering the seasonal changes, we highlight the intensification in the sediment supply and its predominantly sandy composition. They contribute to the current morphological aspects by forming and stabilizing lateral bars and submerging (bed shape) in the secondary channel. In the main channel, marginal dykes and mouth deposits occur at the confluence with the Paraguay River, concomitant with the ecological succession of herbaceous and shrubby species and the hydrodynamic behavior in the dry season. Thus, it is considered that the characterization of the sediments present in the channel deposits, and in the bedforms, corroborated the understanding of the adjustments in its floodplain as processes-response to the input of sediments in the river system.
Keywords: Alluvial Systems; Channel Deposits; Environmental Changes; Connectivity and Hydro-morphodynamic Interactions